What determines intentions to use mobile fitness apps? The independent and joint influence of social norms - Yeoh, Ryna (2023)
To better understand how different psychosocial components motivate the use of mobile fitness apps, this study integrates two major theories in behavior prediction, theory of planned behavior (TPB) and theory of normative social behavior (TNSB). An online survey was conducted with a random sample of undergraduate students (N = 558) registered at a large public university in Singapore. Results show that participants’ outcome expectations, descriptive norms, and perceived behavioral control predicted their intention to use mobile fitness apps, but not injunctive norms. Perceived behavioral control exerted stronger influence on use intention among current users than non-users. In the TPB-TNSB integrated model, group identification significantly moderated the relationship between descriptive norms and use intention, regardless of the user status. This study provides an improved understanding of how components of social influence affect the adoption of mobile fitness app by taking a novel approach to integrate two distinctive theories in behavior prediction.